Analisis Pengaruh Penggunaan Kata Anjay terhadap Kondisi Psikis Generasi-Z - M. Ichsan Nawawi; Risnawati Ibnas; Mahda Al Maidah; Wa Ode Firda Sasmita Darwin; St. Hasna Nurfitriani; Riska Amalia; Mitra Aulia Ramli; Deni Candra (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
Abstract  – The word "anjay" is a multi-situation term, it can be used in a happy atmosphere to anger. The purpose of this study is to find out how Anjay's effect on the psychic condition of Z-generations. The study is a kind of quantitative study using a correlation approach survey method. Z-generations is a research population that is derived from south sulawesi, southeast sulawesi and Java. As many as 100 respondents followed the instruments in charge of questionnaires on Google form to measure whether or not there was an impact between Anjay and his psychic condition. . Based on the value of R2 = 0.019, it was found that the influence of  anjay’s word on the psychological condition of the Z-generation was 1.9%, the rest of the psychological condition was influenced by other causes. Based on the t-test where tcount < ttable which is 1.359 < 1.98447 and F-test where Fcount < Ftable which is 1.847 < 3.94 with a significance value of 0.177 > 0.05 indicates that anjay has no significant effect on psychic conditions. It can be argued that anjay's word was less influential in the psychic condition of Z-generations.Keywords - Anjay, psychological condition, z- generation